How Women’s Community Shape Social Enterprise and it’s Impact? - Chusnul Rofiah (Universitas Negeri Gorontalo, 2022)
This paper aims to present how the strength of the women's community is to solve the problems of economic and nutritional adversity through social enterprises established by the women's community. Moreover women are described as motivated not by reasons of money but rather by a desire to act as what can only be described as the mother of the community: women exist to help, to build, for others but never for themselves, and are rarely valued or rewarded for they job. The methods used in data collection are observation, interviews, and photo documentation. The analysis refers to the hermeneutic phenomenological approach by Van Manen (2001), which describes that researchers